Pratiques et logiques de parents face à l'impératif d'investissement scolaire : l'exemple d'une association d'éducation populaire parisienne - Aline Grasperge (Nantes Université, 2023)
The research discussed in this paper stems from an ongoing thesis project within the theme of partner-ship between educational stakeholders. In an increasingly territorially oriented socio-educational con-text, in which all stakeholders are encouraged to work together for the educational and social success of children and youth, this work contributes to a better understanding of the actions and strategies of parents from working-class backgrounds in supporting and monitoring their children's education, given the growing demand for parental involvement. The study takes place through immersion in a community education organization in the 20th arrondissement of Paris, which is involved in a local contract for educational support (CLAS). This article provides an analysis of approximately forty in-depth interviews conducted with parents seeking assistance from the organization as part of the educational support program, supplemented by materials from participant observations conducted in the association's field.